Transport of thyroid hormones via the choroid plexus into the brain: the roles of transthyretin and thyroid hormone transmembrane transporters - Richardson, Samantha J.; Wijayagunaratne, Roshen C.; D'Souza, Damian G.; Darras, Veerle M.; Van Herck, Stijn L. J. (Frontiers in Neuroscience, 2015)
Thyroid hormones are key players in regulating brain development. Thus, transfer of appropriate quantities of thyroid hormones from the blood into the brain at specific stages of development is critical. The choroid plexus forms the blood-cerebrospinal fluid barrier. In reptiles, birds and mammals, the main protein synthesized and secreted by the choroid plexus is a thyroid hormone distributor protein: transthyretin. This transthyretin is secreted into the cerebrospinal fluid and moves thyroid hormones from the blood into the cerebrospinal fluid. Maximal transthyretin synthesis in the choroid plexus occurs just prior to the period of rapid brain growth, suggesting that choroid plexus-derived transthyretin moves thyroid hormones from blood into cerebrospinal fluid just prior to when thyroid hormones are required for rapid brain growth. The structure of transthyretin has been highly conserved, implying strong selection pressure and an important function. In mammals, transthyretin binds T4 (precursor form of thyroid hormone) with higher affinity than T3 (active form of thyroid hormone). In all other vertebrates, transthyretin binds T3 with higher affinity than T4. As mammals are the exception, we should not base our thinking about the role of transthyretin in the choroid plexus solely on mammalian data. Thyroid hormone transmembrane transporters are involved in moving thyroid hormones into and out of cells and have been identified in many tissues, including the choroid plexus. Thyroid hormones enter the choroid plexus via thyroid hormone transmembrane transporters and leave the choroid plexus to enter the cerebrospinal fluid via either thyroid hormone transmembrane transporters or via choroid plexus-derived transthyretin secreted into the cerebrospinal fluid. The quantitative contribution of each route during development remains to be elucidated. This is part of a review series on ontogeny and phylogeny of brain barrier mechanisms.